HORACIO EN LA LITERATURA ESPAÑOLA: EL PAPEL DE LA TRADUCCIÓN - Rodríguez-Pantoja Márquez, Miguel (Myrtia, 1994)
A brief commentary concerning several spanish translations of same Horace Odes from the Renaissance to the moment. A comparison of different poetical procedures (classical and contemporary metres, reproduction of accentual secuences, isosilabia) has been made. Metrical translations performed by the author are include.